The Gender Leadership Gap: Exploring the Disparities in Leadership Roles (Open Academia: Journal of Scholarly Research, 2023)
Gender disparities in leadership roles persist in various sectors worldwide, with women consistently underrepresented in top positions. This article investigates the gender leadership gap, shedding light on the factors that contribute to these disparities, and the implications for organizations and society. By examining research on the root causes and effects of this gap, we aim to inspire dialogue and action toward achieving greater gender equality in leadership